NILAI PENDIDIKAN KARAKTER PADA ANTOLOGI CERPEN MERAJUT DIRI DALAM LUKISAN CAKRAWALA KARYA AOS MUTQIN, DKK - Hikmah, Faris Nur; Nasikha, Latifatun; Mulasih, Mulasih (DIALEKTIKA JURNAL PENDIDIKAN BAHASA INDONESIA, 2024)
This study aims to describe the character education values contained in the short story anthology Merajut Diri dalam Lukisan Cakrawala by Aos Mutqin, et al. The research was designed using a qualitative approach. The data were collected using the reading and note-taking method and then analyzed descriptively qualitatively. The results showed that there are 12 character education values in the short story anthology Merajut Diri dalam Lukisan Cakrawala, including (1) respect for achievement, (2) friendship (3) honesty, (4) religion, (6) discipline. (7) curiosity, (8) love peace, (9) social care, (10) creativity (11) independence, (12) love to read. Keywords: character, short story, anthology, educational value.